The Effect of Adding Liquid Organic Amino Acid Fertilizer on the Growth and Yield of Pakcoy (Brassica rapa L.) Plants - Solikhah, Afidatus; Purnamasari, Retno Tri; Sulistyawati, Sulistyawati (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2025)
Modern agriculture not only emphasizes increased production, but also environmental sustainability. One effort to support sustainable agriculture is the use of organic fertilizers, including the innovation of amino acid-based liquid organic fertilizers (POC) as an alternative or complement to chemical fertilizers. The research was conducted in the Babatan Hamlet area, Bakalan Village, Bugul Kidul District, Pasuruan City. The research used a non-factorial Randomized Block Design consisting of five treatments and five replications. The treatments were P0: 100% urea fertilizer (control); P1: amino acid concentration 5 ml l-1 + 75% urea; P2: amino acid concentration 10 ml l-1 + 75% urea; P3: amino acid concentration 15 ml l-1 + 75% urea; P4: amino acid concentration 20 ml l-1 + 75% urea. The parameters observed were plant height, number of leaves, leaf area, dry weight of upper plant, dry weight of lower plant, total dry weight of plant, leaf area index (ILD), net assimilation rate (NAR), relative growth rate (RGR), and plant weight-1. Based on the results of the study, it can be concluded that the concentration of amino acids 15 ml l⁻¹ + 75% urea proved to be more effective in increasing the yield and growth of bok choy with a weight of 126.23 g plant-1.